Pengaruh terapi akupunktur pada kualitas tidur pasien nyeri muskuloskeletal kronis - Ningtyas, Ayunda Prisilia Kusuma; Murti, Mehdya Vikia; Tasya, Lisna; Alenta, Aad (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Chronic neuromusculoskeletal pain is pain that lasts more than three months and is often accompanied by sleep disturbances, impacting the sufferer's quality of life. Acupuncture, a complementary therapy, is known to reduce pain and improve sleep quality through nervous system modulation and neurohormonal regulation. Purpose: To determine the effect of acupuncture therapy on sleep quality in patients with chronic neuromusculoskeletal pain. Method: The study used a quasi-experimental design with a pretest–posttest approach and a control group. The sample size was 50 respondents, divided into an experimental group and a control group. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI) before and after the intervention. Results: PSQI score in the experimental group decreased from 11.5 in the pretest to 5.3 in the posttest, indicating an improvement in sleep quality from poor to good. Most respondents in the experimental group were in the good sleep category after the intervention, while the control group remained predominantly in the mild sleep category, with an average PSQI score of 8.2. Conclusion: Acupuncture therapy has been shown to have a positive effect in improving sleep quality in patients with chronic neuromusculoskeletal pain and can be used as a complementary therapy in chronic pain management. Keywords: Acupuncture; Chronic Neuromusculoskeletal Pain; PSQI; Sleep Quality. Pendahuluan: Nyeri neuromuskuloskeletal kronis merupakan nyeri yang berlangsung lebih dari tiga bulan dan sering disertai gangguan kualitas tidur, sehingga berdampak pada kualitas hidup penderita. Terapi akupunktur sebagai terapi komplementer diketahui mampu menurunkan nyeri serta memperbaiki kualitas tidur melalui modulasi sistem saraf dan regulasi neurohormonal. Tujuan: Untuk mengetahui pengaruh terapi akupunktur terhadap kualitas tidur pada pasien dengan nyeri neuromuskuloskeletal kronis. Metode: Penelitian menggunakan desain quasi eksperimen dengan pendekatan pretest–posttest disertai kelompok kontrol. Sampel berjumlah 50 responden yang dibagi menjadi kelompok eksperimen dan kelompok kontrol. Pengukuran kualitas tidur dilakukan menggunakan instrumen Pittsburgh Sleep Quality Index (PSQI) sebelum dan sesudah intervensi. Hasil: Rata-rata skor PSQI pada kelompok eksperimen menurun dari 11.5 saat pretest menjadi 5.3 pada posttest yang menandakan peningkatan kualitas tidur dari kategori buruk menjadi baik. Sebagian besar responden pada kelompok eksperimen berada dalam kategori tidur baik setelah intervensi, sedangkan kelompok kontrol masih didominasi kategori tidur buruk ringan dengan rata-rata skor PSQI sebesar 8.2. Simpulan: Terapi akupunktur terbukti berpengaruh positif dalam meningkatkan kualitas tidur pada pasien dengan nyeri neuromuskuloskeletal kronis dan dapat digunakan sebagai terapi komplementer dalam manajemen nyeri kronis. Kata Kunci: Akupunktur; Kualitas Tidu; Nyeri Neuromuskuloskeletal Kronis; PSQI.